Controlling the orbital angular momentum spectrum of classical and quantum light - Pinnell, Jonathan (My University, 2020)
Harnessing the orbital angular momentum (OAM) of light for fundamental and applicative studies in optics and photonics has witnessed unprecedented growth since the seminal work by Allen et al. in 1992. In recent times, there has been a great deal of investigation into whether optical OAM has the potential to unleash more powerful applications in industry and also reveal fundamental aspects of nature. Indeed, it turns out that utilising this degree of freedom of light can (and does) enhance many key technologies such as communications, cryptography, imaging, micro-manipulation and quantum computing. At a more fundamental level, the OAM of light is also unveiling some crucial aspects about nature itself, such as deblurring the classical-quantum divide. Most often, the main appeal of utilising optical OAM is the unbounded state space it offers; individual photons can, in principle, be made to carry a potentially unbounded amount of information. This is in contrast to the spin angular momentum (SAM) degree of freedom which can only transmit a single bit of information per photon. The spin component of light’s angular momentum was prioritised in the past, owing to the ease and versatility at which it can be manipulated. If the utilisation of the orbital component of light’s angular momentum is to take serious hold, a similar degree of control is a necessity. In particular, what is often most important in applications is the mode distribution: the relative weightings and inter-modal phases of the participating OAM modes, also known as the OAM spectrum of the optical field. However, complete control over the OAM spectrum in the same way as SAM has not yet been mastered. In this dissertation, a means for the arbitrary control of the OAM spectrum of coherent light at the classical, single photon and biphoton entangled regimes is investigated. The techniques and methods presented in this work involve the use of conventional devices such as spatial light modulators (SLMs) and can be enacted in a single shot. As animmediate application, an implementation of a high-dimensional single photon quantum secret sharing protocol is presented, with the largest dimensionality quoted to date and hence the largest potential information capacity per photon. Along the way, several other novel results are showcased, such as the attainment of the largest topological charge vortex beam using SLMs, the measurability and “perfectness” of Perfect Vortex beams, a novel indicator of the self-healing ability of optical beams and the generalisation of spatial filtering to structured light using SLMs. In future work, it is anticipated that the methods presented herein for OAM spectrum control could enable the simulation of certain quantum algorithms using classical light; the benefit being that the steps are done at the speed of light.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science in the Structured Light Laboratory, School of Physics, Faculty of Science, University of the Witwatersrand, Johannesburg, 2020